1982
DOI: 10.1021/jo00340a014
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective control in the alkylation and annelation of anions and dianions derived from 5-norbornene-2,3-dicarboximides

Abstract: Fluorolube provides advantages as the mulling agent, since it is transparent in the region 1400-4000 cm"1, where absorptions due to hydrogen bonding are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Garratt and Hollowood reported that bridgehead functionalization of norbornene derivatives such as endo -5-norbornene-2,3-dicarboximide 5 gave bridgehead alkylated compound 6 with retention of configuration (Scheme 2) [40]. Based on this report, we expected the allyl groups introduced via alkylation sequence will occupy the exo position (see 2ab ) because the bridgehead hydrogens in DA adduct 3a are in exo configuration.…”
Section: Resultsmentioning
confidence: 86%
“…Garratt and Hollowood reported that bridgehead functionalization of norbornene derivatives such as endo -5-norbornene-2,3-dicarboximide 5 gave bridgehead alkylated compound 6 with retention of configuration (Scheme 2) [40]. Based on this report, we expected the allyl groups introduced via alkylation sequence will occupy the exo position (see 2ab ) because the bridgehead hydrogens in DA adduct 3a are in exo configuration.…”
Section: Resultsmentioning
confidence: 86%
“…[12] Consequently, we imagined that reaction of N-substituted succinimides 4 with an excess of a base, such as LDA, and an excess of the alkylating agent 5 might give imides 6 which could be further alkylated to give finally imides 7 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The product was dissolved in CHCl,, decolorized with active charcoal, and crystallized from hexane, mp 132-134°C; ir (CHC13) v: 1765 (s), 1700 (s), 1590 (w) cm-'; 'H nmr (CDCI?) 6: 1.20 (t, J = 7 Hz, 3H), 1.22 (t, J = 7 Hz, 3H), 1.26-1.56 (m, 3H), 1.78-2.00 (m, 3H), 2.14-2.36 (m, 4H), 2.52-2.62 (m, 2H, H4 (7)), 3.51 (q, J = 7 Hz, 2H), 3.52 (q, J = 7 Hz, 2H), 7.20-7.54 (m, 5H); "C nmr (CDCI,) 6: 14.5 (q) and 15.2 (q) (-OCH,CH3), 23.6 (t, C5(6)), 25.4 (t, C9), 34.3 (t, C8(10)), 43.2 (d, C4 (7)), 57.8 (t) and 58.4 (t) (-0CH2CH3), 63.1 (s, C3a (7a) (21) to isolate this compound; I3C nmr (CDCl,) 6: 15.0 (q) and 15.4 (q) (-0CH2CH3), 27.3 (t, C9), 34.1 (t, C8(10)), 52.1 (d, C4 (7)), 58.9 (t) and 60.1 (t) (-0CH2CH3), 63.4 (s, C3a (7a) (7)), 3.37 (q, J = 7.1 Hz, 2H), 3.50 (q, J = 7.1 Hz, 2H), 7.28-7.52 (m, 5H); "C nmr (CDCI,) 6: 15.2 (q) and 15.3 (q) (-0CH2CH3), 21.1 (t, C5 (6)), 28.7 (t, C9), 32.0 (t, C8(10)), 45.5 (d, C4 (7)), 58.3 (t) and 59.1 (t) (-0CH2CH3), 60.4 (s, C3a (7a) propanoisoindol-l,3,Il -trione, 23 A mixture of 3.0 g dicarboximide 22 (8.1 1 mmol) and 60 mL 15% aqueous HC1O4 was heated under reflux for 12 h. The cold mixture was extracted with CHC13 (3 X 50 mL). The combined extracts were washed with water and dried over anhydrous Na2S04.…”
Section: Thermal Decornpositiorz Of the Lithium Salt Of Tosylhydrazonmentioning
confidence: 99%
“…Moreover, a stereoselective synthesis of compound 1 was carried out from the Diels-Alder adduct, 18, between 5,5-diethoxycyclopentadiene and N-phenylmaleimide, as shown in Scheme 5 (published as a preliminary communication (7)). While annelation of the dianion derived from adduct 18 with 1,3-dibromopropane takes place mainly by the endo face (21) to give dicarboximide 19, the corresponding reaction of the dianion derived from (3aR,4S,7R,7aS)-8,8-diethoxy-2-phenyl3a,5,6,7a-tetrahydro-1 H,3H-4,7-methanoisoindol-1,3-dione, 21, takes place preferently by the exo face to give (3aR,4S, 7R,7aS)-1 1,l l-diethoxy-5,6-dihydr0-2-phenyl-lH,3H-4,7-methano-3a,7a-propanoisoindol-1,3-dione, 22. The configuration of compound 22 was clearly established (7) by comparison of its I3C nmr spectrum with that of (3aR,4R,7S,7aS)-11,l l-diethoxy-5,6-dihydro-2-phenyl-1H,3H-4,7-methano3a,7a-propanoisoindol-1,3-dione, 20, obtained by hydrogenation of compound 19.…”
mentioning
confidence: 99%